Tailoring the mechanical property and cell-biological response of β-tricalcium phosphate composite bioceramics by SrO-P2O5-Na2O based additive. (October 2018) - He, Fupo; Lu, Teliang; Tian, Ye; Li, Xue; Zuo, Fei; Shi, Xuetao; Ye, Jiandong
Abstract: β-tricalcium phosphate (β-TCP) bioceramic, which is a prevalent bone graft, is deficient in mechanical strength and mediating the biological functions. In the present study, β-tricalcium phosphate composite bioceramics (TCP/SPNs) were prepared by introducing SrO-P2 O5 -Na2 O based (SPN) sintering additive. With increasing mole ratio of SrO to P2 O5, the SPN tended to crystallize. In the liquid-phase sintering process, β-TCP reacted with SPN, producing new compounds. The difference in characteristic of SPN additive affected the compressive strength and cell-biological response of the fabricated TCP/SPNs. By selecting SPN with appropriate formulation, the TCP/SPNs not only could more than double their compressive strength, but also improved the cell viability, promoted osteogenic differentiation and inhibited osteoclastic activities. Taken together, this work establishes a beneficial strategy to improve the overall performance of calcium phosphate bioceramic for application in bone regeneration.